2015
DOI: 10.1017/s0033291715000045
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa and body dysmorphic disorder are associated with abnormalities in processing visual information

Abstract: Background Anorexia nervosa (AN) and body dysmorphic disorder (BDD) are characterized by distorted body image and are frequently comorbid with each other, although their relationship remains little studied. While there is evidence of abnormalities in visual and visuospatial processing in both disorders, no study has directly compared the two. We used two complementary modalities – event-related potentials (ERP) and fMRI – to test for abnormal activity associated with early visual signaling. Methods We acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 47 publications
6
74
1
2
Order By: Relevance
“…Previous brain imaging studies in BDD have shown aberrant patterns of hypoactivation in visual systems for low detail (LSF) images of own face, familiar face, and object stimuli . As mentioned above, a study that included AN and BDD showed that both groups, compared to HC, displayed hypoactivity in the dorsal ventral stream and early secondary visual processing regions when viewing LSF faces . While future studies will be required to investigate this, these results may reflect common, diminished global and holistic information processing, uncovered by the same LSF image “probes” as in the current study, which could contribute to facial perception that is lower in attractiveness.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Previous brain imaging studies in BDD have shown aberrant patterns of hypoactivation in visual systems for low detail (LSF) images of own face, familiar face, and object stimuli . As mentioned above, a study that included AN and BDD showed that both groups, compared to HC, displayed hypoactivity in the dorsal ventral stream and early secondary visual processing regions when viewing LSF faces . While future studies will be required to investigate this, these results may reflect common, diminished global and holistic information processing, uncovered by the same LSF image “probes” as in the current study, which could contribute to facial perception that is lower in attractiveness.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, AN and BDD exhibit similar abnormalities in appearance valuations that extend beyond themselves to others' appearance, and for physical features that are related and unrelated to their primary appearance concern. Our recent imaging data (the results of which were available only after we had formulated hypotheses and conducted the current study) might suggest that the neural underpinnings of this finding could be related to a common abnormality in visual processing of emotion‐neutral stimuli, but this idea should be considered with circumspection given that we did not directly measure neural responses in this study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Three recent studies have compared their neurobiology related to brain activation and connectivity in response to visual stimuli (Li et al 2015a; Li et al 2015b; Moody et al 2015), but none have investigated their brain structural connectome using state-of-the-art analytics of modularity analysis. To explore similarities and differences in brain connectivity, we analyzed whole-brain tractography-derived networks (i.e., structural connectomes) using graph theory, which quantifies complex networks or “graphs” to provide information about their organizational properties.…”
Section: Introductionmentioning
confidence: 99%